Lipidomic characteristics and clinical findings of epileptic patients treated with valproic acid. Issue 9 (4th June 2019) - Li, Rong; Qin, Xingyue; Liang, Xiaoliu; Liu, Meizhen; Zhang, Xiaoxi
Abstract: Our early study has found valproic acid (VPA)‐induced lipid dysmetabolism in animal model, however, the details of lipid profiling of VPA‐treated epileptic patients remain unknown. Therefore, in this study, the blood samples of VPA‐treated epileptic patients and VPA‐free controls were collected for lipidomic and biochemical assays. As results, clinical data showed the changes of some blood lipid molecules in VPA‐treated epileptic patients. In lipidomic assays, all 3797 annotated positive ions were identified prior to the data validation. In addition, the number of differentially expressed lipids were identified. And the 133 lipid molecules in VPA‐treated cases were significantly up‐regulated when compared to those in controls, while other 250 lipid metabolites were down‐regulated. Further, these lipid metabolites were mainly constituted with glycerolipids, glycerophopholipids, fatty acyls, sterol lipids. In addition, the most significant elevations of metabolite molecules of triglyceride, sphingomyelin, phosphorylcholine, ceramides, phenolic phthiocerol, as well as topped reductions of phosphoethanolamines, diradylglycerols, 1α, 25‐dihydroxy‐24‐oxo‐22‐oxavitamin D3, 2‐deoxy‐20‐hydroxy‐5alpha‐ecdysone 3‐acetate, dolichyl‐4 phosphate were identified respectively. Taken together, these clinical findings demonstrate that negative impacts of exposure to VPA on expression of lipid mediators, progressively disrupting the functions of lipid molecules. Interestingly, these differentially expressed metabolites may be potential biomarkers for screening VPA‐induced dyslipidemia.